(untitled) (Research, Society and Development, 2022)
The study of solar reflectance and therefore the albedo is essential for bifacial photovoltaic systems to estimate their performance. To meet this need, two pyranometers were installed, one observing the direct and the other the reflected solar radiation, in order to obtain data on the albedo of the ground during the experimental activity. The albedo of the ground surface is an important factor in the cost-benefit ratio of a bifacial photovoltaic system. The measured data sets include albedo time series in the monthly and hourly period, for the period 2022. Preliminary results indicated for a typical soil, Eutrophic Red Latosol, which presents a clayey to moderate texture, an albedo value of 0.15 with a measurement uncertainty of ±0.02. The data aims to facilitate the understanding of albedo values and the characteristics required, both for the use in a bifacial photovoltaic project installed on site, for its future financial analysis, and to better estimate the performance and reduce the risk of system deployment.